Pengaruh Motivasi dan Intensitas Belajar di Rumah terhadap Prestasi Belajar Aqidah Akhlak : (Studi Kasus di MI Miftahul Ulum Tunahan 03 Jepara) - Sukarman Sukarman; Nima Marfuatin (STAI Attanwir Bojonegoro, 2022)
The purpose of this study was to determine: (1) learning motivation Aqidah Akhlak MI students Miftahul Ulum Tunahan 03 (2) Knowing the intensity of learning at home in the Aqeedah Akhlak subjects MI Miftahul Ulum Tunahan 03 students (3) learning achievement Aqidah Akhlak subjects MI Miftahul Ulum Tunahan 03 students (4) the influence of motivation and intensity of learning at home on learning achievement Aqidah Akhlak MI Miftahul Ulum Tunahan 03 students. Data collection techniques use: observation to collect learning motivation data, questionnaires for data on learning intensity at home and tests to collect learning achievement data Aqidah Akhlak. The population of MI Miftahul Ulum Tunahan students is 2018/2019 academic year, amounting to 104 people, because the population is widely sampled classically in class IV and V students, amounting to 25 people. Statistical analysis using multiple regression formulas. The results show that simultaneously there is a significant positive effect of learning motivation and intensity of learning at home on learning achievement Aqidah Akhlak MI Miftahul Ulum Tunahan 03 students. Based on statistical analysis with multiple regression formulas showed a significance level of 5% or 1%. Where the magnitude of Freg is 11.13 then compared with Ftable with df = 2: 22, for a significance level of 1% = 5.72 and for a significance level of 5% = 3.44. So Freg> F table. Stelain was also found to be determined by 58%, which means that motivation and intensity of learning at home had a positive effect of approximately 58% on Aqidah Akhlak learning achievement.